2020
DOI: 10.1111/jvh.13430
|View full text |Cite
|
Sign up to set email alerts
|

Global evolutionary analysis of chronic hepatitis C patients revealed significant effect of baseline viral resistance, including novel non‐target sites, for DAA‐based treatment and retreatment outcome

Abstract: Direct-acting antivirals (DAAs) have proven highly effective against chronic hepatitis C virus (HCV) infection. However, some patients experience treatment failure, associated with resistance-associated substitutions (RASs). Our aim was to investigate the complete viral coding sequence in hepatitis C patients treated with DAAs to identify RASs and the effects of treatment on the viral population. We selected 22 HCV patients with sustained virologic response (SVR) to match 21 treatment-failure patients in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 43 publications
2
10
0
Order By: Relevance
“…This suggests that NS5A RAS could be a concern for short‐term treatment, but testing for baseline RAS will not be a realistic option in a clinical setting. The most important baseline RAS associated with treatment failures are located in NS5A domain I 18 . These also affected RNA titer decline and quasi‐species composition after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This suggests that NS5A RAS could be a concern for short‐term treatment, but testing for baseline RAS will not be a realistic option in a clinical setting. The most important baseline RAS associated with treatment failures are located in NS5A domain I 18 . These also affected RNA titer decline and quasi‐species composition after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The most important baseline RAS associated with treatment failures are located in NS5A domain I. 18 These also affected RNA titer decline and quasi-species composition after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This effect may be more evident in less potent treatments such as SOF + RBV ± INF and can efficiently be counteracted in pan-genotypic regimens that include several potent DAA that can more rapidly inhibit viral replication. Another study has also identified sites outside the NS5B associated with sofosbuvir-based treatment outcome, including sites in similar regions of the NS2 and NS3 protein 35 . However, this was in gt1a HCV and in a cohort with only 20 patients.…”
Section: Discussionmentioning
confidence: 99%